2023
DOI: 10.3389/fpls.2023.1163270
|View full text |Cite
|
Sign up to set email alerts
|

Plant protection from virus: a review of different approaches

Irina Anikina,
Aidana Kamarova,
Kuralay Issayeva
et al.

Abstract: This review analyzes methods for controlling plant viral infection. The high harmfulness of viral diseases and the peculiarities of viral pathogenesis impose special requirements regarding developing methods to prevent phytoviruses. The control of viral infection is complicated by the rapid evolution, variability of viruses, and the peculiarities of their pathogenesis. Viral infection in plants is a complex interdependent process. The creation of transgenic varieties has caused much hope in the fight against v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Effects of virus infection in the plant can include damage to the root system, interference with nutrient transport, changes in mineral metabolism ( Mishra et al., 2020 ), and disruption of hormonal regulation ( Llave, 2016 ), promoting an imbalance between the leaf (source) and the root system ( Anikina et al., 2023 ). These changes can lead to nutrient deficiencies, affecting the growth and development of sweet potato storage roots ( Clark et al., 2012 ; Ogero et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of virus infection in the plant can include damage to the root system, interference with nutrient transport, changes in mineral metabolism ( Mishra et al., 2020 ), and disruption of hormonal regulation ( Llave, 2016 ), promoting an imbalance between the leaf (source) and the root system ( Anikina et al., 2023 ). These changes can lead to nutrient deficiencies, affecting the growth and development of sweet potato storage roots ( Clark et al., 2012 ; Ogero et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, a number of studies have demonstrated that transgenic approaches, especially by enhancing RNA silencing against viral RNA sequences, can provide effective plant protection against viruses [ 141 ]. Due to public concerns and strict regulatory barriers, this approach has been restricted for field use.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition, cross-protection is another efficient strategy without genetic modification, which is able to fight against severe virus strains. Reverse genetics can be adopted to generate attenuated mutants that have potential in cross-protection against tobamoviruses [ 141 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Most viral diseases are characterized by systemic damage, in which the virus spreads from the primary site of inoculation to other parts of the plant until it dies off once the plant is infected. It is passed to the offspring by vegetative propagation (Anikina et al 2023 ). Symptoms of viral infections typically include developmental abnormalities, necrosis, and chlorosis (Wang et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, managing disease focuses on keeping viruses out of plants or making plants resistant to viral infection. To do this, several tactics that are tailored to each virus, host and environment must be created (Rubio et al 2020 ; Anikina et al 2023 ). Agrochemicals are commonly used to suppress plant virus infection, but these methods are unacceptably expensive and may have negative environmental implications.…”
Section: Introductionmentioning
confidence: 99%